The Effect Of Diorama Learning Media On Student Learning Outcomes In Pkn Class IV - Bthalia Margaretha Siburian; Sukardo Sitohang; Osco Parmonangan Sijabat (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine the effect of diorama learning media on student learning outcomes in Civics Lessons for Fourth Graders at the UPTD of Public Elementary School 125549 Pematangsiantar. This study used a quantitative research method with a "Pre-Experimental Design" in the form of a One Group Pre-test Posttest. This study was conducted at the UPTD of Public Elementary School 125549 Pematangsiantar on fourth grade students with a population of 23 and a sample of 25. The data collection technique for this study used two tests, namely a pretest and a posttest. The data were processed using statistical analysis techniques. Hypothesis testing showed a significant effect in this study from the data that had been tested. The data analysis obtained the average pretest results (54.60) and posttest (83.20). Based on the results of this study, it can be concluded that there is an Effect of Diorama Learning Media on Student Learning Outcomes in Civics Learning for Class IV of UPTD SD Negeri 125549. This is also proven by the results of the data analysis test obtained a significance level of 0.000 <probability (0.05) and t count -9.737 t table 1.711. Therefore, it is concluded that Ho is rejected and Ha is accepted, which means "The Effect of Diorama Learning Media on Student Learning Outcomes in Civics Learning for Class IV of UPTD SD Negeri 125549 Pematangsiantar"